Peripheral blood biomarkers for the characterization of alloimmune reactivity after pediatric liver transplantation. (6th October 2013) - Briem‐Richter, Andrea; Leuschner, Alexander; Krieger, Thorsten; Grabhorn, Enke; Fischer, Lutz; Nashan, Bjoern; Haag, Friedrich; Ganschow, Rainer
Abstract: Individualization of immunosuppressive medications is an important objective in transplantation medicine. Reliable biomarkers to distinguish between patients dependent from intensive immunosuppressive therapy and those where therapy can be minimized among pediatric transplant recipients receiving immunosuppressive medications are still not established. We evaluated the potential of cross‐sectional quantification of regulatory T cells, lymphocyte subsets, and cytokine concentrations as biomarkers in 60 pediatric liver transplant recipients with AR, CR, or normal graft function and in 11 non‐transplanted patients. Transplant recipients presenting with AR had significantly higher CD8 + T‐cell counts, significantly higher concentrations of IL‐2, and increased levels of IFN‐γ compared with asymptomatic patients or controls. Regulatory T‐cell numbers did not differ between children with rejection and children with good graft function. A tendency toward increased concentrations of IL‐4 and TGF‐β was detected in transplant recipients with good graft function. Cross‐sectional parameters of peripheral regulatory T cells in pediatric liver transplant recipients do not seem to be valuable biomarkers for individualizing immunosuppressive therapy prior to the weaning process. Lymphocyte subsets, IL‐2, IFN‐γ, IL‐4, and TGF‐β serum concentrations may be helpful to identify children in whom immunosuppression can be reduced or discontinued.